Minimally invasive versus traditional inverted “L” approach for posterior cruciate ligament avulsion fractures: a retrospective study - Yao Zhao; Huihui Guo; Liang Gao; Chang Liu; Xinzhong Xu; Wendan Cheng (PeerJ, 2022)
Purpose To evaluate the clinical efficacy of a minimally invasive arthroscopic approach and to compare it with the traditional inverted “L” approach for the treatment of posterior cruciate ligament (PCL) avulsion fractures. Methods From January 2016 to January 2020, the clinical data from patients with PCL avulsion fracture of the tibial insertion were analyzed retrospectively. They were divided into two groups based on surgical approaches: minimally invasive approach group (n = 15) and traditional inverted “L” group (n = 15 cases). The operation time, incision length, intraoperative blood loss, hospitalization time and complications were all recorded and compared between the two groups. The fracture healing time, knee range of motion (ROM), and residual relaxation degree were compared between the two groups after regular follow-up. The International Knee Documentation Committee (IKDC) and Lysholm scores were used to assess knee joint function. Results There were no significant differences between the two groups in terms of gender, age, side, body mass index, cause of injury, Meyers McKeever classification and time from injury to operation (P > 0.05). The incision length and intraoperative bleeding in the minimally invasive group were significantly lower (P < 0.05) than those in the traditional group. There were no significant differences between the two groups in terms of operative time, fracture healing time, or residual relaxation (P > 0.05). The Lachman test and posterior drawer test were both negative, and there were no postoperative complications. The VAS pain score within 2 weeks and ROM within 4 weeks in the minimally invasive group were significantly better (P < 0.05) than those in the traditional inverted “L” approach group. The knee joint stability of both groups was good 12 months after surgery, and there were no significant differences in IKDC score, Lysholm score and ROM (P > 0.05) between the two groups. Conclusion The minimally invasive approaches for the treatment of PCL avulsion fractures provide adequate exposure without the surgical complications associated with traditional open surgical approaches. The procedure is safe, fast and minimally invasive, and does not need a long learning curve.